1997
DOI: 10.1080/15216549700202271
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA primase by sphingosine and its analogues parallels with their growth suppression of cultured human leukemic cells

Abstract: Sphingosine is a potent inhibitor of a mammalian DNA primase in vitro (Simbulan et al., Biochemistry 33, 9007‐9012, 1994). Here we measured the inhibition of DNA primase in vitro by 9 sphingosine‐analogues with respect to RNA primer synthesis and DNA primase‐dependent DNA synthesis, and their potencies of inhibition in vitro were compared with their in vivo effects on human leukemic cells. Sphingosine, phytosphingosine and N, N‐dimethylsphingosine strongly inhibited the activity of purified calf thymus DNA pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 7 publications
1
43
0
Order By: Relevance
“…In this respect, the phytoceramide nature of the C. albicans PLM lipid moiety raises an important question (26). Although our knowledge of phytoceramide and phytosphingosine synthesis or hydrolysis is still embryonic, the presence of these molecules in mammalian cells has been demonstrated, and several studies have suggested that, like ceramide, phytosphingosine may play an important role in cell growth or death of eukaryotic cells (56,57). Due to their critical role in cell integrity, it is interesting to note that ceramide biosynthetic pathways are also critical for the establishment of fungal pathogens in the host.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the phytoceramide nature of the C. albicans PLM lipid moiety raises an important question (26). Although our knowledge of phytoceramide and phytosphingosine synthesis or hydrolysis is still embryonic, the presence of these molecules in mammalian cells has been demonstrated, and several studies have suggested that, like ceramide, phytosphingosine may play an important role in cell growth or death of eukaryotic cells (56,57). Due to their critical role in cell integrity, it is interesting to note that ceramide biosynthetic pathways are also critical for the establishment of fungal pathogens in the host.…”
Section: Discussionmentioning
confidence: 99%
“…(23) Moreover, sphingosine inhibits RNA primers and DNA primers, but not DNA polymerases, to induce cell death. (19,24) However, the study of another sphingosine analog, phytosphingosine, has recently begun.In the present study, we therefore examined the precise mechanism of phytosphingosine-mediated apoptosis in T-cell lymphoma Jurkat cells in comparison with sphingosine. It was found that phytosphingosine, almost identically to sphingosine, significantly induces apoptosis in Jurkat cells.…”
mentioning
confidence: 99%
“…(23) Moreover, sphingosine inhibits RNA primers and DNA primers, but not DNA polymerases, to induce cell death. (19,24) However, the study of another sphingosine analog, phytosphingosine, has recently begun.…”
mentioning
confidence: 99%
“…DNA primase activity of pol α and the activities of T7 RNA polymerase, human DNA topoisomerases I and II, T4 polynucleotide kinase and bovine deoxyribonuclease I were measured using standard assays according to the manufacturer's specifications as described by Tamiya-Koizumi et al (28), Nakayama and Saneyoshi (29), Mizushina et al (30), Soltis and Uhlenbeck (31) and Lu and Sakaguchi (32), respectively.…”
Section: Methodsmentioning
confidence: 99%